Robotics for inclusive education: Combining active methodologies in a classroom - Castañeda Rincón, Silvino Antonio; Moreno Gudino, Hayarelis; Gil Herrera, Richard de Jesús (Contemporary Educational Technology, 2025)
In light of the growing diversity of students in the classroom, there is a pressing need to address the potential for discrimination against minorities, arising from cultural, socioeconomic, special needs, learning styles, and other differences. It is, therefore, essential to establish inclusive learning environments that guarantee equitable learning outcomes for all children and young people. This study aims to determine the impact of educational robotics (ER) in promoting emotional, cognitive, and social inclusion attributes through active methodologies among secondary students in public institutions. The applied methodology is composed of elements typical of active methodologies implemented in education and cited in the theoretical framework. The instruments employed to measure the classroom intervention process across various stages demonstrated a gradual improvement in the reference attributes of inclusive education. The findings suggest that ER can serve as a valuable tool for promoting inclusion in diversity contexts.
Keywords: diversity; educational robotics; educational technology; inclusion